Normative preconditions for the assessment of mental disorder - Stier, Marco (Frontiers in Psychology, 2013)
The debate about the relevance of values for the concept of a mental disorder has quite a long history. In the light of newer insights into neuroscience and molecular biology it is necessary to re-evaluate this issue. Since the medical model in previous decades was more of a confession rather than evidence based, one could assume that it is – due to scientific progress – currently becoming the one and only bedrock of psychiatry. This article argues that this would be a misapprehension of the normative constitution of the assessment of human behavior. The claim made here is twofold: First, whether something is a mental disease can only be determined on the mental level. This is so because we can only call behavior deviant by comparing it to non-deviant behavior, i.e. by using norms regarding behavior. Second, from this it follows that psychiatric disorders cannot be completely reduced to the physical level even if mental processes and states as such might be completely reducible to brain functions.